Multi-parametric whole-body MRI evaluation discerns vital from non-vital multiple myeloma lesions as validated by 18F-FDG and 11C-methionine PET/CT. Issue 155 (October 2022) - Heidemeier, Anke; Schloetelburg, Wiebke; Thurner, Annette; Metz, Corona; Heidemeier, Heike; Rasche, Leo; Martin Kortuem, K.; Boeckle, David; Weiland, Elisabeth; Benkert, Thomas; Nickel, Dominik; Werner, Rudolf; et al.
Graphical abstract: Highlights: Multi-parametric whole-body MRI facilitates a reproducible, standardized whole-body MR analysis in multiple myeloma. A prototypical DIXON-type sequence allows for fat quantification on automatically generated fat fraction maps. Substantial concordance between MRI classification of lesions and PET assessment according to Deauville criteria. Abstract: Purpose: We tested a novel multi-parametric (mp) whole body (WB)-MRI evaluation algorithm for medullary lesions in comparison to positron emission tomography (PET) radiotracers 18 F-fluorodeoxyglucose ( 18 F-FDG) and 11 C-methionine ( 11 C-MET). Methods and Materials: This retrospective single-center study included 44 MM patients, who received both 18 F-FDG-PET and WB-MRI within ten days. MRI classified focal lesions as vital when showing 1) significant diffusion-restriction, 2) a fat fraction (FF) less than 20 % and 3) homogenous hypointensity on T2-weighted images. On a lesion-by-lesion level the findings were compared to 18 F-FDG PET by using a 5-point scoring system (analogous to the Deauville score [DS]). In 24/44 (55 %) patients additional comparison to 11 C-MET PET was available. Results: Among two radiologists, an excellent inter-observer reliability for mpWB-MRI in a total of 84 medullary lesions was observed (ICC = 1, k  = 1, p <.01). 16/17 (94.1 %) MRI-classified vital lesions had a DS of 4 or 5 on either 18 F-FDG-PET or 11 C-MET-PET. MRI-rated non-vital lesions correlated with PET-based DS ≤ 3. When results of mpWB-MRI were compared to 18 F-FDG, a fair inter-observer agreement was recorded (ICC = 0.52, k  = 0.53, p <.01), while for 11 C-MET, an excellent concordance rate was achieved (ICC = 0.81, k  = 0.79, p <.01). Conclusion: The proposed mpWB-MRI interpretation algorithm allowed to assess tumor activity of myeloma lesions with high inter-observer reproducibility. We observed a substantial concordance between the mpWB-MRI classification of lesions and PET assessment based on a semi-automatically calculated 5-point scoring system analogous to the Deauville scores.